The Role of Microglia in Perioperative Neurocognitive Disorders - Fan, Wenguo; Mai, Lijia; Zhu, Xiao; Huang, Fang; He, Hongwen (Frontiers in Cellular Neuroscience, 2020)
Perioperative neurocognitive disorder (PND) is a common phenomenon associated with anesthesia and surgery and has been frequently described in the elderly and susceptible individuals. Microglia, which are the brain’s major resident immune cells, play critical roles in maintaining neuronal homeostasis and synaptic plasticity. Accumulating evidence suggests microglial dysfunction occurring after anesthesia and surgery might perturb neuronal function and induce PND. This review aims to provide an overview of the involvement of microglia in PND to date. Possible cellular and molecular mechanisms regarding the connection between microglial activation and PND are discussed.